Sonaten für Pianoforte allein componirt von L. van Beethoven. Billigste und correcte Ausgabe mit gestochenen Noten ... op. 101. Sonate, A. - Beethoven, Ludwig van, 1770-1827 (composer):::Creator:::::::::::: (Germany; Johann André; Offenbach am Main, 2022)
Lithographed edition of the Piano Sonata no. 28 in A major, op. 101, with a decorative collective title page for the "Sonaten für Pianoforte allein" that lists the Fantasie in G major, op. 77, and the Sonatas opp. 78, 79, 81[a], 90, and 101; variant with plate number "T.1." Includes metronome markings.